A new planthopper species in the genus Omolicna (Hemiptera: Auchenorrhyncha: Derbidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2021)
Recent survey work on palms in Costa Rica has resulted in the discovery of several new species of Derbidae, especially in the Cenchreini. During a recent expedition, specimens collected by light trapping at the Hotel Villa Blanca (cloud forest) were determined to be a novel species of Omolicna Fennah. Sequence data was generated for the novel taxon for the cytochrome c oxidase subunit I (COI) and 18S loci. Pairwise analyses and phylogenetic analyses support placement of the novel taxon in Omolicna.